Modeling and comparative analysis of solar drying behavior of potatoes. (January 2020) - Djebli, Ahmed; Hanini, Salah; Badaoui, Ouassila; Haddad, Brahim; Benhamou, Amina
Abstract: Potatoes are a very high demand product in the consumer market and are widely available everywhere in Algeria. With the extensive levels of solar energy across the country, solar drying becomes a natural avenue for the production of solar dried potatoes as a new prospective commercial product. This paper is a study of the drying process of potatoes using an indirect and a mixed solar dryer with forced convection and a comparison of their respective performances. Experimental results indicated that the mixed solar dryer had the slowest drying rate compared to the indirect solar dryer with drying times of 4 h 45min and 3 h 40min respectively, even though the temperature at the tray level in the mixed solar dryer was higher than that of the indirect solar dryer. Fourier series and Laplace transforms were used to solve the diffusivity equation. Seven theoretical models were investigated and their relative accuracy validated against experimental data. Two new dimensionless models were found to best fit the drying curve of potato slices using the two dryers. The proposed models were found to be more accurate for charactering the drying process of Sultana grapes, chili peppers, bananas, mangoes and cassava, according to models reported in the literature under different operating conditions using various solar dryer designs. Highlights: This study used an indirect solar dryer and mixed solar dryer to dry potato slices. Mixed solar dryer has a better thermal efficiency, and the lowest drying time. Fourier series and Laplace transforms were used to solve the diffusivity equation. The new models perfectly describe the solar drying behavior of different products. The new universal models are independent of dryers design and operating conditions.